Aplikasi Kamus ViKA sebagai Visualitator Kosakata Bahasa Arab untuk Pembelajar Pemula - Lia Sunarti; Ernawati Ernawati; Marja’i Affan (IAIN Salatiga, 2017)
This research aims to produce a digital dictionary ViKA (Visualitation by Creation and Action) as media for for beginner learners to understand the meaning of Arabic vocabulary according the morphology (Creation) and syntax (Action). This Research and Development uses quantitative data for the analysis with the independent variables